Evidences of non-LTE emission in the ISAMS water vapour channels - Zaragoza, G; Lopez-Puertas, M; Lambert, A; Remedios, J; Taylor, F (1999)
An analysis of the day-night enhancements on the 6.9 mu m H2O emission measured by the Improved Stratospheric and Mesospheric Sounder (ISAMS) on the Upper Atmospher Research Sounder (UARS) is presented. A characterization of these differences With parameters such as the solar zenith angle (SZA) and kinetic temperature has been done and explained in terms of atmospheric processes by using a non-LTE radiative transfer model. The goal of these continuing studies is to implement these non-LTE effects in the operational retrieval of H2O. (C) 1999 COSPAR. Published by Elsevier Science Ltd.